Model Hidrologi Produksi Air Bulanan Bagian II : Analisis Korelasi Antara Parameter Model dan Karakteristik DAS - Lukman Hidayat; Putu Sudira; Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
An automatic parameter optimization routine was presented. Eleven small watersheds (less than 1000 square km) in Central Java were used for calibration. A method for estimating four parameters water yield model was obtained Equations for predicting the parameters were developed on the correlation analysis between model parameters and measurable watershed characteristics.